HUBUNGAN INDEKS MASSA TUBUH DENGAN KADAR ALBUMIN PADA PENDERITA TUBERKULOSIS PARU YANG MENJALANI TERAPI OBAT ANTI TUBERKULOSIS (OAT) DI RUMAHSAKIT BENYAMIN GULUH KOLAKA - Kemal Idris Balaka; Apriyanto Apriyanto; Indriani Ishar (Jurnal Analis Kesehatan Kendari, 2023)
Albumin is one indicator of malnutrition (malnutrition), both at the beginning of the incidence of malnutrition and when repairs begin to occur. Tuberculosis is a contagious infectious disease caused by the bacterium Mycobacterium tuberculosis, which can attack various organs, especially the lungs. Tuberculosis itself, besides being able to affect the lungs can also affect the Body Mass Index. Because every decrease in body mass index occurs there is a decrease in albumin levels.This study aims to determine the relationship between the Body Mass Index and Albumin levels in patients with pulmonary tuberculosis who underwent OAT therapy at Benyamin Guluh Kolaka Hospital. This type of research is observational analytic using the Erba XL 100 cresol green bromine method with accidental sampling technique. The number of samples is 22 people.The results of the study of 22 patients with pulmonary tuberculosis patients who were taking anti-tuberculosis drugs (OAT) at Benyamin Guluh Kolaka Hospital obtained albumin levels in 13 men (59.09%) and 9 women (40.91%). After the correlation test was obtained, the p-value was 0.110 (p> 0.05), the hypothesis (H0) was accepted, namely there was no relationship between body mass index and albumin level in pulmonary tuberculosis patients at Benyamin Guluh Kolaka Hospital. Keywords : Pulmonary Tuberculosis, Albumin